Integrating Pancasila and Islamic Economics: Formulating an Indonesian Hybrid Economic Paradigm through the OPOP Model - Sifwa (al-Uqud : Journal of Islamic Economics, 2026)
Indonesia’s development trajectory has long been constrained by a structural dichotomy between capitalism and socialism, limiting opportunities to construct a value-based economic framework grounded in the nation’s philosophical and religious heritage. This condition has contributed to widening social inequality and recurring economic injustice, underscoring the urgency of an alternative paradigm that integrates ethical foundations and local wisdom. This study critically examines the normative compatibility between the Pancasila Economic System and Islamic Economics, proposing an integrative model as an Indonesian hybrid economic paradigm. Using a qualitative library-based method and comparative analysis of academic literature, constitutional documents, and empirical studies, the research identifies strong convergences in distributive justice, communal solidarity, democratic economic governance, and the protective role of the state. At the empirical level, the One Pesantren One Product (OPOP) program in East Java is analyzed as a concrete expression of the synergy between Pancasila and Islamic values through pesantren-based entrepreneurship, social capital enhancement, and community-driven economic development. Theoretically, the study advances an integrative framework that enriches global discussions on value-based and faith-informed development models. Practically, it offers policy insights for strengthening state support, enhancing pesantren institutional capacity, and reducing the dominance of capitalist market forces in national development. The novelty of this research lies in its comprehensive approach that links philosophical principles, cultural traditions, and empirical evidence into a coherent model for inclusive and justice-oriented economic development in Indonesia.